2015
DOI: 10.1128/aem.01856-15
|View full text |Cite
|
Sign up to set email alerts
|

Geogenic Factors as Drivers of Microbial Community Diversity in Soils Overlying Polymetallic Deposits

Abstract: dThis study shows that the geogenic factors landform, lithology, and underlying mineral deposits (expressed by elevated metal concentrations in overlying soils) are key drivers of microbial community diversity in naturally metal-rich Australian soils with different land uses, i.e., agriculture versus natural bushland. One hundred sixty-eight soil samples were obtained from two metal-rich provinces in Australia, i.e., the Fifield Au-Pt field (New South Wales) and the Hillside Cu-Au-U rare-earth-element (REE) de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 58 publications
5
14
0
Order By: Relevance
“…The strong influence of pH on bacterial communities is suggested to be due to the narrow pH ranges for optimal growth of bacteria, as opposed to the weaker influence on fungi which exhibit in general a wider pH tolerance (Rousk et al, 2010). The importance of parent material on composition of bacterial communities has already been reported for other cold ecosystems (Lazzaro et al, 2009; Larouche et al, 2012; Reith et al, 2015; Tytgat et al, 2016; Yashiro et al, 2016; Li et al, 2018). Parent material and soil pH are closely related since bedrock, soil age (years of weathering) and plant cover influence soil pH (Lazzaro et al, 2009).…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…The strong influence of pH on bacterial communities is suggested to be due to the narrow pH ranges for optimal growth of bacteria, as opposed to the weaker influence on fungi which exhibit in general a wider pH tolerance (Rousk et al, 2010). The importance of parent material on composition of bacterial communities has already been reported for other cold ecosystems (Lazzaro et al, 2009; Larouche et al, 2012; Reith et al, 2015; Tytgat et al, 2016; Yashiro et al, 2016; Li et al, 2018). Parent material and soil pH are closely related since bedrock, soil age (years of weathering) and plant cover influence soil pH (Lazzaro et al, 2009).…”
Section: Discussionsupporting
confidence: 53%
“…Elevation-dependent effects on composition of microbial communities across mountain environments can further be confounded by parent material in alpine ecosystems (Lazzaro et al, 2009; Larouche et al, 2012; Shen et al, 2013; Reith et al, 2015). In addition, slope aspect and exposition (Zumsteg et al, 2013; Liu L. et al, 2015; Frey et al, 2016; Wu et al, 2017; Chai et al, 2018) can modify elevational patterns as soil temperatures can vary considerably over distances of only a few metres (Scherrer and Körner, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…For example, the elements As, Ba, Cr, Cu, Ge, and Zn significantly contributed to the differences in prokaryotic community structures in both hypersaline sediments and saline soils. Our findings are supported by research showing that microelements, including As, Cr, Cu, and Zn, affected bacterial community structures in coastal sediments and metal-rich soils ( Quero et al, 2015 ; Reith et al, 2015 ). The combined microelements (As, Ba, Cr, Cu, Ge, and Zn) and variables (Cr and Cu) individually explained 21.28% and 6.93% of the total variation in community structures of prokaryotes and fungi ( Figure 6 ), indicating the relative importance of micronutrients in modulating prokaryotic composition.…”
Section: Discussionsupporting
confidence: 86%
“…Although some microelements are regarded as toxic to most forms of life, they regulated microbial communities in extreme conditions. For instance, they are significantly correlated with bacterial community composition in hot springs ( Jiang et al, 2016 ) and certain elements (Co, Ni, and Mn) explained variations of prokaryotic and fungal assemblages in polymetallic mining areas ( Reith et al, 2015 ). These previous studies have enriched our knowledge of microbial biogeography, but the respective reports are mainly focused on various macroelements.…”
Section: Introductionmentioning
confidence: 99%
“… 14 In Australia, high metal contents in soils overlying mineral deposits were discriminatory for a variety of bacterial taxa, including Acidobacteria, Bacilli, Betaproteobacteria, and Epsilonproteobacteria. 16 However, this is also true for many other environments, like oil reservoirs or contaminated groundwater what seems that genera/species within these phyla are established in many diverse environments. Also Hill et al 17 based on an analysis for a broad range of environmental samples, suggested that actinobacterial community structure seems to be selected by human and animal activities.…”
mentioning
confidence: 99%